Who Is Centered? A Systematic Review of Early Childhood Researchers' Descriptions of Children and Caregivers From Linguistically Minoritized Communities. (May 2021) - Soto-Boykin, Xigrid T.; Larson, Anne L.; Olszewski, Arnold; Velury, Veena; Feldberg, Anna
Young children with and without disabilities who are bilingual or in the process of learning multiple languages have many strengths; however, educational policies and bias related to bilingualism for children from linguistically minoritized groups have typically included deficit-based views. The purpose of this systematic review was to identify how researchers describe these children and their caregivers. Thirty research studies were included in the review. Each study was published in Infants and Young Children, Journal of Early Intervention, or Topics in Early Childhood Special Education between 1988 and 2020. Studies were coded to determine participant characteristics and whether deficit- or strength-based descriptions of participants were used. Although researchers' descriptions of participants' linguistic backgrounds varied, most were English-centric, and deficit-based descriptions of bilingualism were more prevalent than strength-based descriptions. Preliminary recommendations are provided for describing children and families from linguistically minoritized communities and including strength-based language in research and practice.